Tramadol use and risk of seizure: A report of two cases and a review of recent literature - Emma Dolan; Norman Delanty (Epilepsy & Behavior Reports)
Tramadol is a common pain medication used in practice across numerous specialties. Increased incidence of tramadol abuse and overdose in recent decades has led to it being classified as a controlled drug in several countries. Tramadol appears to be an increasingly popular drug of abuse, possibly related to ease of access to it on prescription, and its potential euphoric effects.We identified two cases of seizures directly related to tramadol exposure. We then reviewed recent literature on tramadol and its adverse effects, particularly looking at its effect on seizure risk and the incidence of seizures. We found that there were scarce recent studies on the relationship between tramadol and seizure risk. Of studies found, many were carried out in animal models. Tramadol-induced seizures were studied in humans more commonly in the context of overdose, and studies involving humans tended to have small patient cohorts and suggested further study in the area.We suggest that tramadol may be useful as part of multi-modal analgesia in moderate to severe pain in specific contexts, but that greater awareness of its potential adverse effects, and particularly its potential to lower seizure threshold, is warranted. We feel that more readily available information specifically about tramadol’s effects on seizure threshold may be of interest to colleagues from any specialty prescribing opioid analgesia on a regular basis, but that colleagues treating patients with seizure disorders should be particularly aware of these potential adverse effects.